Community Supported Fisheries: Establishing New Markets in a Limited Resource Industry. - Cooke, Bronwyn. (2017)
Abstract: Abstract Current conditions in the fishing industry are threatening fishing livelihoods and the communities that rely on them. The overfishing that has reduced fish stocks and the regulations enacted to better conserve what fish stocks remain have made it difficult for small fishing operations to maintain fishing livelihoods. Small fishing operations are further disadvantaged by concentration in the industry which makes it difficult to remain competitive in the traditional market place dominated by large, industrial fishing operations. In response to these conditions, alternative markets called Community Supported Fisheries, have emerged as a way of maintaining fishing livelihoods. Although it is still early in their development, Community Supported Fisheries (CSFs) hold much potential. Case studies on three New England CSFs indicate that they may be able to provide local economic benefits, such as paying fishermen a better price per pound for their fish and supporting the local economy through partnerships. CSFs may also be able to provide conservation benefits such as reducing fishing pressure on overfished species by creating a stronger market for underutilized species. Collaboration and strong monitoring and evaluation plans are needed to help CSFs become a viable alternative market that supports small fishing operations and local fishing communities.  ; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Ann Rappaport, and Francine Jacobs.; Keywords: Fisheries and aquatic sciences, Environmental management, and Sustainability.